Letter from President's Advisory Committee on Political Refugees - United States. President's Advisory Committee on Political Refugees (1941)
In an effort to secure the immigration of Dr. Alfred Reis (1882-1951), Hans A. Straus writes to suggest copies of Reis's immigration paperwork be sent to both Reis' French addres as well as to Professor K. F. Herzfeld of Catholic University in Washington D.C.
Keywords: United States. President's Advisory Committee on Political Refugees; Bredig, Max Albert, 1902-1977; Reis, Alfred J., 1882-1951; Refugees; Emigration and immigration